2003
DOI: 10.1007/s00441-003-0708-2
|View full text |Cite
|
Sign up to set email alerts
|

Lead nitrate and gadolinium chloride administration modify hepatocyte cell surfaces

Abstract: Modifications of hepatocyte cell surface were determined after single i.v. injection to rats of Pb(NO 3 ) 2 (known to induce liver hyperplasia followed by apoptosis) or GdCl 3 (known to induce proliferation of parenchymal cells and Kupffer cell depletion) or administration of GdCl 3 24 h before Pb(NO 3 ) 2 injection (known to reduce hyperplasia and apoptosis induced in the parenchymal liver cells by the single Pb(NO 3 ) 2 injection). Rats were sacrificed at fixed times after the treatments (1, 3 and 5 days) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…This result is in agreement with the study undertaken by Patra et al [13], who recorded an increase in MDA content in the liver and the brain of rats subjected to subchronic exposure to lead for a period of four weeks. Pagliara et al [43] showed that lead-induced liver hyperplasia was followed by apoptosis mediated by oxidative stress in Kupffer cells. The group treated with 5 mg Pb/kg b.w [Pb 5] recorded no changes in MDA content in liver compared to controls, suggesting that this may be due to the short duration of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the study undertaken by Patra et al [13], who recorded an increase in MDA content in the liver and the brain of rats subjected to subchronic exposure to lead for a period of four weeks. Pagliara et al [43] showed that lead-induced liver hyperplasia was followed by apoptosis mediated by oxidative stress in Kupffer cells. The group treated with 5 mg Pb/kg b.w [Pb 5] recorded no changes in MDA content in liver compared to controls, suggesting that this may be due to the short duration of the treatment.…”
Section: Discussionmentioning
confidence: 99%